Interaksi Obat Potensial pada Sirosis Hati: Tinjauan Pola dan Faktor Sosiodemografi - Amni , Hudiyah; Fitria, Najmiatul; Sari, Yelly Oktavia (Journal of Pharmaceutical and Sciences, 2025)
Liver cirrhosis is a chronic condition characterised by the formation of regenerative nodules and fibrotic tissue resulting from prolonged liver damage. This condition is frequently accompanied by comorbidities and complications, often leading to the use of multiple medications (polypharmacy). Polypharmacy increases the risk of potential drug interactions, which may worsen clinical outcomes. This study aimed to describe the patterns of possible drug interactions and the sociodemographic characteristics of hospitalised patients with cirrhosis at Dr M. Djamil Central General Hospital in Padang. A cross-sectional study was conducted using prospectively collected data from patient medical records. A total of 579 medications used by 50 patients were classified into three categories: cirrhosis-specific drugs (48.9%), symptomatic treatments (43.2%), and medications for comorbid conditions (7.95%). Analysis with drugs.com showed potential drug interactions in 96% of patients, most commonly moderate–to–minor combinations (48%), followed by major, moderate, and minor interactions (22%). In comparison, moderate interactions only and major moderate combinations occurred in 18% and 9% of patients, respectively.  In terms of sociodemographic characteristics, most patients were male (58%), under 65 years old (64%), had more than one comorbidity (52%), had a basic education level (32%), were still employed (56%), and did not engage in high-risk social behaviors such as smoking or alcohol consumption (48%).